Performance evaluation of LTE scheduling techniques for heterogeneous traffic and different mobility scenarios - Sukeran, Lukmanhakim; Habaebi, Mohamed Hadi; Zyoud, Al-Hareth; Musse, Mohamud Ahmed; Hameed, Shihab A.; Azman, Amelia Wong; Islam, Md. Rafiqul (2014)
In this paper five scheduling algorithms were investigated and their performance was evaluated in terms of Fairness Index, Peak Throughput, Average Throughput and Edge Cell User Throughput. A system level MATLAB simulator was used. The simulation takes into account different types of traffic for several mobility scenarios and propagation channel models. Results indicate that the scheduling algorithms showed some quality in certain parameter of evaluation but lack in other terms. While some scheduling algorithm take the moderate path but still be lacking especially in Edge Cell User Throughput necessitating the use of Relays or femtocells.